STRATEGI IMPLEMENTASI & OPTIMALISASI MANAJEMEN ENERGI DI PT SEMEN PADANG SEBAGAI UPAYA KEUNGGULAN BERSAING DI INDUSTRI PERSEMENAN NASIONAL - Dasril, Arief Rahman; Lukman, Syukri (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Energy is a determining factor in the company's efforts to be superior in the national cement industry competition. If we look at the factor of total production costs COGM (Cost Of Goods Manufactured) in the last five years, the portion of energy costs always occupies the top position with a percentage of 45% - 52% of the total cost of cement production. Therefore, in order to win the competition in the cement industry, it is necessary to manage energy consumption more effectively and efficiently. This study aims to determine the contribution of the implementation energy management system at PT Semen Padang as an effort to reduce energy consumption in the cement production process. The results of this study indicate that the implementation of the energy management system at PT Semen Padang has a significant impact on reducing energy consumption and increasing the company's competitive advantage so that it has an impact on increasing the bottom line of PT Semen Padang. Key Word : Competitive Advantage, Energy Management, Firm Performance, Cement Industry